2018
DOI: 10.1111/iwj.12933
|View full text |Cite
|
Sign up to set email alerts
|

Exercise fidelity and progression in a supervised exercise programme for adults with venous leg ulcers

Abstract: Despite exercise being included in the recommended advice for patients with venous leg ulcers, there is a fear shared by clinicians and patients that exercise may be either inappropriate or harmful and actually delay rather than promote healing. Therefore, before implementing a larger-scale study exploring the effects of a supervised exercise programme in patients with venous ulcers being treated with compression therapy, it is important to assess exercise safety as well as fidelity and progression in a feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…After excluding 135 duplicate studies and ineligible studies (77 reviews, 18 case reports, 3 animal studies, 18 conference abstracts, 172 irrelevant records), a total of 100 studies were evaluated for eligibility in the next step of screening. After full‐text review of 28 articles, we finally identified eight randomised control studies that met the inclusion criteria, including a total of 270 patients with diagnosed VLU 32‐39 . Details on literature search is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding 135 duplicate studies and ineligible studies (77 reviews, 18 case reports, 3 animal studies, 18 conference abstracts, 172 irrelevant records), a total of 100 studies were evaluated for eligibility in the next step of screening. After full‐text review of 28 articles, we finally identified eight randomised control studies that met the inclusion criteria, including a total of 270 patients with diagnosed VLU 32‐39 . Details on literature search is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After full‐text review of 28 articles, we finally identified eight randomised control studies that met the inclusion criteria, including a total of 270 patients with diagnosed VLU. 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 Details on literature search is depicted in Figure 1 . The year of publication for included studies ranged from 2010 to 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research team involved in the evaluative work did not have influence over the content of the sessions delivered, as this was an existing community-based Public Health initiative. A worthwhile aspect for the Vitality program would be to consider evaluating the exercise progression and fidelity of new but also existing members, which has occurred in other exercise interventions for older adults [ 43 ]. It should be acknowledged that whilst participants in both the VP and CON groups were instructed not to participate in any additional daily physical activity, this was not monitored during the study period.…”
Section: Discussionmentioning
confidence: 99%